Spleen Stiffness Measurement as a Predictor of Advanced Liver Fibrosis in Chronic Hepatitis B Patients - Carisa Irene Hertanto; Ummi Maimunah; Aryati -; Muhammad Miftahussurur (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2025)
Background: Chronic hepatitis B is a viral infection that may progress to liver fibrosis. Progressive fibrosis increases portal pressure, leading to elevated spleen stiffness. Although inflammatory reactions and mechanical cholestasis affect liver stiffness, the effect is comparatively limited. Therefore, this study aims to analyze spleen stiffness as a noninvasive marker of liver fibrosis and evaluate the correlation between spleen and liver stiffness.Methods: A retrospective cross-sectional study was performed on chronic hepatitis B patients. Fibroscan was used to measure liver and spleen stiffness. Liver fibrosis was categorized as nonsignificant (F0–F1), significant (F2–F3), and advanced (F4). Correlations between spleen stiffness and liver fibrosis stages were assessed using Spearman’s test, with p 0.05 considered statistically significant. Results: The results showed that 127 patients were eligible for analysis, predominantly male (71.7%), with a mean age of 46.4 ± 9.8 years. The median spleen and liver stiffness were 25.5 kPa (range 5.6–100) and 9.4 kPa (range 2.4–75), respectively. Moreover, spleen stiffness had a positive correlation with liver stiffness (Spearman r = 0.503; p 0.001) and liver fibrosis stages (Spearman r = 0.479; p 0.001). The optimal cutoff for spleen stiffness in predicting advanced fibrosis was 28 kPa, with an area under the receiver operating characteristic curve(AUROC) of 0.816, sensitivity of 0.739, and specificity of 0.753.Conclusion: Spleen stiffness is significantly correlated with liver fibrosis severity. A cutoff of 28 kPa was identified for advanced fibrosis, suggesting spleen stiffness measurement serves as a promising alternative to biopsy.